The prevalence rates and adversities of delirium: Too common and disadvantageous. Issue 2 (April 2021) - Boettger, Soenke; Zipser, Carl Moritz; Bode, Leonie; Spiller, Tobias; Deuel, Jeremy; Osterhoff, Georg; Ernst, Jutta; Petry, Heidi; Volbracht, Joerk; von Känel, Roland
Abstract: Objective: The prevalence rates and adversities of delirium have not yet been systematically evaluated and are based on selected populations, limited sample sizes, and pooled studies. Therefore, this study assesses the prevalence rates and outcome of and odds ratios for managing services for delirium. Methods: In this prospective cohort study, based on the Diagnostic and Statistical Manual (DSM) 5, the Delirium Observation Screening (DOS) scale, and the Intensive Care Delirium Screening Checklist (ICDSC) construct, 28, 118 patients from 35 managing services were included, and the prevalence rates and adverse outcomes were determined by simple logistic regressions and their corresponding odds ratios (ORs). Results: Delirious patients were older, admitted from institutions (OR 3.44–5.2), admitted as emergencies (OR 1.87), hospitalized twice longer, and discharged, transferred to institutions (OR 5.47–6.6) rather than home (OR 0.1), or deceased (OR 43.88). The rate of undiagnosed delirium was 84.2%. The highest prevalence rates were recorded in the intensive care units (47.1–84.2%, pooled 67.9%); in the majority of medical services, rates ranged from 20% to 40% (pooled 26.2%), except, at both ends, palliative care (55.9%), endocrinology (8%), and rheumatology (4.4%). Conversely, in surgery and its related services, prevalence rates were lower (pooled 13.1%), except for cardio- and neurosurgical services (53.3% and 46.4%); the lowest prevalence rate was recorded in obstetrics (2%). Significance of results: Delirium remains underdiagnosed, and novel screening approaches are required. Furthermore, this study identified the impact of delirium on patients, determined the prevalence rates for 32 services, and elucidated the association between individual services and delirium.